ANALISIS PERHITUNGAN DAN PELAPORAN PAJAK ATAS PENEBUSAN LPG 3KG DARI PERTAMINA PADA PT. BERKAT JABES - Corneles, Vrenshit Merdekhawati; Ilat, Ventje; Tirayoh, Victorina Z. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2014)
Government program over the transition from oil fuel to gas fuel since 2007 has made PT. Berkat Jabes that had worked as kerosene dealer, turned to join as LPG dealer, especially 3kg LPG as from May 2012. For each purchase/redemption of 3kg LPG PT. Berkat Jabes have to pay Income Tax article 22 at the rate of 0,3% and 10% VAT. The objective of this study is to analyze the calculation and reporting tax of the purchased of 3kg LPG if it is in accordance with the provisions of the applicable tax. The method that has been used in this research is descriptive quantitative. Quantitatve data that obtained by the author was processed and analyzed to describe the process of calculating and reporting tax by PT. Berkat Jabes. The result from the research showed that PT. Berkat Jabes has fully run their tax obligation, but still need to complete the documents upon the payment of Income Tax article 22 and VAT and make the right accounting records based on the transactions of purchase/redemption that have occurred.